A new lizard species of the Phymaturus patagonicus group (Squamata: Liolaemini) from northern Patagonia, Neuquén, Argentina - Marín, Andrea González; Pérez, Cristian Hernán Fulvio; Minoli, Ignacio; Morando, Mariana; Avila, Luciano Javier (Zootaxa, 2016)
The integrative taxonomy framework allows developing robust hypotheses of species limits based on the integration of results from different data sets and analytical methods. In this work, we test a candidate species hypothesis previously suggested based on molecular data, with geometric and traditional morphometrics analyses (multivariate and univariate). This new lizard species is part of the Phymaturus patagonicus group (payuniae clade) that is distributed in Neuquén and Mendoza provinces (Argentina). Our results showed that Phymaturus rahuensis sp. nov. differs from the other species of the payuniae clade by a higher number of midbody scales, and fewer supralabials scales, finger lamellae and toe lamellae. Also, its multidimensional spaces, both based on continuous lineal variables and geometric morphometrics (shape) characters, do not overlap with those of the other species in this clade. The results of the morphometric and geometric morphometric analyses presented here, coupled with previously published molecular data, represent three independent lines of evidence that support the diagnosis of this new taxon.